Steady state and dynamic hygrothermal performance of rendered straw bale walls. Issue 1 (11th February 2019) - Thomson, Andrew; Dick, Kris; Walker, Pete
Abstract : Wheat straw, in the form of compacted bales, is increasingly used as thermal insulation in the external walls of buildings. Common practice is to use a render or plaster finish, applied directly to the external and internal surfaces of the straw bales, to protect them from decay, and to enhance structural performance and fire resistance. Coatings are typically made of water vapour permeable materials, such as lime or earth based render and plaster formulations. Such coatings should allow water vapour to diffuse through, minimising the risk of liquid moisture build up within the thickness of the wall and so reducing likelihood of decay. However, to date there has been very limited scientific study of this behaviour in rendered straw bale walls. The aim of the work presented in this paper was to develop understanding of the hygrothermal performance of lime rendered wheat straw bale walls. A test panel was subjected to a unique range varying environmental conditions, including a thermal shock, dynamic freeze thaw exposure and hot humid conditions. Key scientific contributions of this work also include data on both the dynamic and steady state hygrothermal characteristics of a wheat straw bale wall, combined with the application of heat and moisture modelling. This work will further support uptake of straw bale construction by designers and their wider use in energy efficient construction projects.